A new genus of hell ants from the Cretaceous (Hymenoptera: Formicidae: Haidomyrmecini) with a novel head structure. (4th September 2017) - Barden, Phillip; Herhold, Hollister W.; Grimaldi, David A.
Abstract: An unusual Cretaceous trap jaw ant is described from Burmese amber dated to the Late Cretaceous. Linguamyrmex vladi gen.n. sp.n. is distinguished by an unusual suite of morphological characters indicating specialized predatory behaviour and an adaptive strategy no longer found among modern ant lineages. The clypeus, highly modified as in other closely related haidomyrmecine hell ants, is equipped with a paddle‐like projection similar to Ceratomyrmex . X‐ray imaging reveals that this clypeal paddle is reinforced, most probably with sequestered metals. Presumably this fortified clypeal structure was utilized in tandem with scythe‐like mandibles to pin and potentially puncture soft‐bodied prey. This unique taxon, which stresses the diversity of stem‐group ants, is discussed in the context of modern and other Cretaceous trap jaw ant species. This published work has been registered in ZooBank, http://zoobank.org/urn:lsid:zoobank.org:pub:40D636A3‐4D88‐470A‐BC5B‐85ABFD1A49E2 . Abstract : Linguamyrmex vladi, a new species and genus of 'hell ant', is described from Late Cretaceous Burmese amber. Linguamyrmex vladi possesses an unusually modified paddle-like cranial appendage, derived from a clypeal expansion, along with characteristic scythe-shaped mandibles that typify hell ant taxa. This paddle‐like appendage appears to be reinforced, indicating that it was probably used to help with prey capture.